2012
DOI: 10.3138/ptc.2010-54
|View full text |Cite
|
Sign up to set email alerts
|

The Diagnostic Validity of Clinical Tests in Temporomandibular Internal Derangement: A Systematic Review and Meta-analysis

Abstract: Purpose: To assess the diagnostic validity of clinical tests for temporomandibular internal derangement relative to magnetic resonance imaging (MRI). Methods: MEDLINE and Embase were searched from 1994 through 2009. Independent reviewers conducted study selection; risk of bias was assessed using Quality Assessment of studies of Diagnostic Accuracy included in Systematic reviews (QUADAS); b9/14) and data abstraction. Overall quality of evidence was profiled using Grading of Recommendations Assessment, Developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…Recent studies highlighted that clinicians should look at a combination of assessment tests and functional tests for the diagnosis of musculoskeletal conditions such as patellofemoral pain syndrome, 25 cervicogenic headache26,39 or shoulder pain 27. This was in accordance with the literature, where combinations of symptoms and a clinical test were considered to have a moderate to high reliability (k-values >0.4).This combination of tests assisted the clinician to sub-classify the patients' presentation into arthrogenic, myogenic or neurogenic TMD 24,28. For example, when assessing cervical impairment, expertspreferred the craniocervical flexion test (endurance) and cervical spine screening with manual techniques.…”
supporting
confidence: 58%
“…Recent studies highlighted that clinicians should look at a combination of assessment tests and functional tests for the diagnosis of musculoskeletal conditions such as patellofemoral pain syndrome, 25 cervicogenic headache26,39 or shoulder pain 27. This was in accordance with the literature, where combinations of symptoms and a clinical test were considered to have a moderate to high reliability (k-values >0.4).This combination of tests assisted the clinician to sub-classify the patients' presentation into arthrogenic, myogenic or neurogenic TMD 24,28. For example, when assessing cervical impairment, expertspreferred the craniocervical flexion test (endurance) and cervical spine screening with manual techniques.…”
supporting
confidence: 58%
“…Palpation-tests in other body areas, however, are considered as subjective with low reliability (Billis et al, 2003;Seffinger et al, 2004;Robinson et al, 2007). Previously Chaput et al (2012) have suggested that a cluster of clinical…”
Section: Discussionmentioning
confidence: 99%
“…The present study was planned in accordance with the present recommendations (Chaput et al, 2012); describing the patient population, blinded assessments for both the clinical tests and MRIs and a definition of the diagnostic test. All of which are important to avoid systematic error.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations